Tindak Tutur dalam Iklan Lebaran Mr.Diy 2022 “Kembali Ke Pangkuan” - Wibisono Yudhi Kurniawan (GERAM: Gerakan Aktif Menulis, 2023)
Advertising is one of the strategies employed by producers to promote their products or services. The purpose of this research is to analyze the discourse in the MR.DIY 2022 Eid advertisement "Kembali ke Pangkuan" available on the MR DIY Indonesia YouTube channel. The study aims to describe and identify the types of discourse and their functions in the advertisement. This research adopts a qualitative approach, and the research data consist of speech fragments that reflect illocutionary speech acts. The data source for this study is a video recording of the advertisement. Data collection was conducted using observation and note-taking techniques (advanced techniques). Data analysis was performed using a qualitative data analysis model according to Miles and Huberman, which involved data reduction, data presentation, and data inference. The findings of this study indicate the presence of 22 illocutionary speech acts in the MR.DIY 2022 Eid advertisement "Kembali ke Pangkuan". The types of utterances include: (1) 4 instances of assertive speech acts, (2) 7 instances of directive speech acts, (3) 7 instances of expressive speech acts, (4) 3 instances of commissive speech acts, and (5) 1 instance of declaration speech act.